The Role of products of Microfinance for Reducing the Poverty of the Borrowers: Exploratory Factor Analysis - Kumari, J.A Prasansha (International Journal of Management Excellence (ISSN: 2292-1648), 2020)
This paper intend to analyses the structural characteristics of microfinance and statistically categorized them in to five products of microfinance as independent variable and poverty reduction as dependent variable. Data were gathered from 494 borrowers of Samurdhi microfinance program in five districts in Sri Lanka using Likert scale questionnaire. The collected data analyzed by Exploratory Factor analysis using SPSS 21 version. The factor Metrix of the EFA results presented good pattern distribution among 38 items which indicated that six constructs loaded properly which is greater than acceptable threshold >0.5. Therefore, the results explored that the 38 items can be grouped properly into the six constructs based on their items.